1974
DOI: 10.1177/00220345740530023801
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Fluoride on LS Cells

Abstract: The fluoride sensitivity and the lethal concentration of LS cells were determined. The cells were adapted to grow in the presence of lethal concentrations of fluoride. The adaptation persisted after removal of fluoride. Any possible binding of the fluoride to medium components was excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

1977
1977
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 9 publications
2
18
1
Order By: Relevance
“…acting upon any component in serum, in agreement with previous reports (Hongslo et at. 1974;Ekstrand et al 1977).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…acting upon any component in serum, in agreement with previous reports (Hongslo et at. 1974;Ekstrand et al 1977).…”
Section: Resultssupporting
confidence: 93%
“…Fluoride inhibition of protein and DNA synthesis correlates well with its growth inhibiting effect. As no other parameter, such as metabolism and ATP content (Holland & Hongslo 1978& 1979a, uptake and pools of amino acids (Holland & Hongslo 1979b), Na', K+ levels (Quissell & Suttie 1973), is significantly affected at such low fluoride concentrations as presently found to inhibit protein and DNA synthesis, it seems probable that these are the main targets for the cytotoxic action of fluoride. This is consistent with results recently published by Mankowitz et al (1978).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies in 1970s reported that by stepwise increase in fluoride concentration, cells adapted to grow at fluoride concentrations that would kill them . Several types of cells (e.g., L cells, LS cells, Hela cells, and CHO cells) that retained their vitality in lethal concentrations of fluoride were developed by slowly increasing the concentration of fluoride . However, due to limitations in research methodology, no further research was performed at molecular level to investigate mechanisms associated with the observation of fluoride resistance of cells.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of fluoride application has been a controversial and political process which has centered around questions of biological risks involved when the fluoride is used in the public water supply (Richmond 1985). In this context, fluoride cytotoxicity was mostly of concern and was examined by numerous earlier workers using established aneuploid cell lines (Carlson & Suttie 1967;Hongslo et al 1974;Oguro et al 1982). However, its effect on growth of human diploid cells, as normal cell model, is less known (Tsutsui et al 1984).…”
mentioning
confidence: 99%